The Experience Of The Intensive Care Unit In A British Army Field Hospital During The 2003 Gulf Conflict. Issue 4 (1st December 2003) - Roberts, MJ; Fox, MA; Hamilton-Davies, C; Dowson, S
Abstract : Over the last few years the Surgeon General's Department has overseen a major update in equipment scales for medical units in the field; anaesthesia and intensive care. This is to meet the aspiration of the Defence Chiefs, that injured servicemen on active service should receive the same standard of care as available in the United Kingdom. This paper discusses the experiences of the Intensive Care Unit operating within a Field Hospital both during the initial war fighting phase and subsequent peace keeping phase of the 2003 Gulf conflict (OP TELIC). Observations are made on patient activity, treatment strategy, and equipment adequacy.